MESOPOTAMIAN DROUGHT UNDER THE POLICIES OF NEIGHBORING COUNTRIES AND THE STRATEGIC WATER CRISIS FOR IRAQ - Dr. Ghodrat Ahmadian; Dr.Farzad Rostami; Saeed Mohammed (Journals Park Publishing, 2022)
The Mesopotamian civilization of present-day Iraq, the first civilization in history, began to build systems that control water resources through an extensive network of irrigation canals and flood control regulators, prompting scientists and researchers to launch a new concept in the Mesopotamian community. This is a "hydraulic community." On the banks of the two great Tigris and Euphrates rivers in this region, the development of tools for the construction and development of human civilization began, such as books, irrigation systems, trade, and commodity exchanges and their standards, building cities, enacting laws, arithmetic methods, mathematics, and astronomy . It should be said that these tools are the foundations on which the late and present civilizations were built .
Keywords: Iraq; Strategy; Drought